Evaluation of risk factors for early complications following bowel anastomosis - Islam, A. K. M. Zahedul; Hossain, M. Farhad; Sultana, Masuma; Islam, M. Oliul; Ahmad, Tanvir; Haque, M. Jayer (International Surgery Journal, 2025)
Background: In emergency as well as in elective situations, gastrointestinal anastomosis is an essential step to maintain the continuity of gastrointestinal tract following intestinal resection. Anastomotic complications, primarily, anastomotic leaks is one of the most widely feared and extensively studied problems in GI surgery. That’s why this study was conducted to identify the risk factors for early complications in gastrointestinal anastomosis Methods: This was a cross sectional observational Study which took place in the department of Surgery, Rangpur Medical College Hospital and private hospitals in Rangpur, Bangladesh from 1st October 2018 to 31st March 2019 over a period of 6 months. All statistical analysis was performed using the SPPS software program version 26.0 (SPSS, Inc., Chicago, IL, United States of America). A p value<0.05 was considered statistically significant. Results: A total number of 200 patients were included in the study by purposive sampling method. Mean age of the study population was 46±13.6 years with a male female ratio of 2:1. Among them 44% patients had gastro-jejunal anastomosis and 66% patients had anastomosis involving small and large gut. Anastomotic leaks (AL), (4.5%) and hemorrhage (2.2%) were the main post-operative complications. Re-operation was required in 3.5% patients. Operative mortality rate was 5.5%, with 06 deaths (54%) secondary to anastomotic complications. Univariate analysis of the overall population male patient, age, malnutrition, malignancy, sepsis and uses of steroids were independent predictors of postoperative complication following gastrointestinal anastomosis. Conclusions: Anastomotic complications, particularly anastomotic leaks, remain a major unsolved problem in GI surgery.